2019
DOI: 10.1016/j.memsci.2018.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of pore fouling by colloidal particles at the particle level

Abstract: Particle filtration occurs whenever particles flow through porous media such as membrane. Progressive capture or deposition of particles inside porous structure often leads to complete, and generally unwanted, fouling of the pores. Previously there has been no experimental work that has determined the particle dynamics of such a process at the pore level, since imaging the particles individually within the pores remains a challenge. Here, we overcome this issue by flowing fluorescently dyed particles through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Besides the hydrodynamic effect, surface patterning affects the foulant by preventing deposition of particles on the valleys if the particle size is bigger than the valley size or by altering the particle crystallization entropy when the size is about similar. Membrane surface patterning induces turbulence via local mixing near the membrane surface, requiring lower linear velocity and thus lowering the pressure loss along the module [7,41,42,43,44,45]. This advantage makes membrane surface patterning gain more attention of researchers to explore all its possible application opportunities.…”
Section: Membrane Surface Patterningmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the hydrodynamic effect, surface patterning affects the foulant by preventing deposition of particles on the valleys if the particle size is bigger than the valley size or by altering the particle crystallization entropy when the size is about similar. Membrane surface patterning induces turbulence via local mixing near the membrane surface, requiring lower linear velocity and thus lowering the pressure loss along the module [7,41,42,43,44,45]. This advantage makes membrane surface patterning gain more attention of researchers to explore all its possible application opportunities.…”
Section: Membrane Surface Patterningmentioning
confidence: 99%
“…Membrane–mold adhesion during demolding affects the structure and the smoothness of the membrane surface which hinders its wide application in liquid separation processes due to the presence of a boundary layer. Membrane surface roughness facilitates accumulation of colloidal particles in the valley areas [7,43].…”
Section: Membrane Surface Patterningmentioning
confidence: 99%
“…To study the behavior of such real-world soft filter cakes with their complex composition, synthetic soft colloids with previously established properties have been used as model foulants in several experimental and theoretical simulation studies 39 . Depending on their size, these synthetic soft colloids represent ideal entities to mimic the mechanical and hydraulic properties of soft biological matter, ranging from proteins to cells and biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Until this issue is adequately addressed, microfluidic platforms may continue to suffer from a low adoption rate. As a result, there has been a push to understand the complex problem of clogging at the single‐pore and even single‐particle level, to better predict and model the growth of clogs . All of these fundamental clogging studies have focused on steady flow, but recent reports have found that clogging can be effectively mitigated with the aid of oscillatory perturbations.…”
Section: Pulsatile Flows In Microfluidic Processesmentioning
confidence: 99%